Mechanical Properties and Fire Resistance of 3D-Printed Cementitious Composites with Plastic Waste - Walid Yaqub; Farhad Aslani (International Journal of Concrete Structures and Materials)
Abstract The study focuses on the development of cementitious composites using 3D printing and plastic waste as a sustainable aggregate substitute. This study involves experimenting with various percentages of plastic waste as a partial substitute for ground granulated blast furnace slag (GGBFS) in a control mix. The study examines the anisotropy of the 3D printing process, comparing it with properties of mold-cast samples. In addition, it assesses the fire resistance and mechanical properties of samples at elevated temperatures (100 °C, 300 °C, and 600 °C). Key mechanical properties, including 28-day compressive stress and flexural strength, are determined through experimental testing using a standard compression test and three-point bending test. The study also considers the modulus of elasticity (MOE) in compressive tests to evaluate a sample’s ability to deform elastically and the flexural toughness index to assess energy absorption and crack resistance of flexural samples. Following the experimental testing, the study’s key findings suggest that significant mass loss occurred at 300 °C and above, with plastic samples demonstrating increased mass loss at 600 °C. At 600 °C, plastic degradation led to the formation of voids and cracks within samples due to heightened internal pressure. Anisotropy was evident in 3D-printed samples, with loads parallel to the layer direction resulting in greater compressive strength and MOE. Furthermore, layer direction parallel to the longitudinal axis of flexural samples yielded higher flexural strength and flexural toughness. Mold-cast samples displayed superior compressive strength and stiffer behavior, with higher MOE compared to 3D-printed samples. However, 3D-printed plastic samples exhibited superior flexural strength compared to mold-cast samples, attributed to the alignment of plastic within the samples. The study also observed a reduction in compressive strength with the addition of plastic, explained by the poor bonding of plastic with cement due to its hydrophobic nature. Despite this, flexural strength generally improved with plastic addition, except at 600 °C, where plastic samples showed significant degradation in both compressive and flexural strength due to plastic degradation within the samples.